Behavior characteristics of parents engaged in child-rearing, in relation to their personality and children's personality - Haruki, Y.; Ohashi, Y.; Fukui, I.; Kanno, J.; Shigehisa, T. (Japanese Journal of Behavior Therapy, 1991)
Parents' personality and rearing attitudes in terms of the mode of reinforcement were investigated in relation to their children's personality. Subjects were 245 Japanese 9-year-old boys and girls, who answered questionnaires deviced to determine personality and the reinforcement modes of their own and, their parents. Children's and parents' personalty were determined on the scores of the dimensions of : extraversion (Ex), emotionality (Em), toughmindedness (To) dissimulation (Di), and self-actualization/altruism (Sa), of the WPQ (revised version of the EPQ). Parents' rearing attitudes were determined on the scores of the modes of : forcing reinforcement (Fr), leaving reinforcement (Lr), catching reinforcement (Cr), and admitting reinforcement (Adr), of the IRS (Interpersonal Relationship Schedule). Significant correlations were found primarily between : (1) children's Ex and father's Ex (2) childen's Sa and mothers' To, fathers' Em, To, (3) childrens' Ex and mothers' Fr, Adr, fathers' Fr. These results suggested a paradigm for genetic-environmental interaction, in terms of parents' parsonality and rearing attitudes, in children's personality.